Host-specific monogeneans parasitizing freshwater fish: The ecology and evolution of host-parasite associations - Šimková, Andrea (Parasite (Paris, France), 2024)
Monogenea (Platyhelminthes), mainly gill and fin ectoparasites of fish, are often recognized as host specific and morphologically and ecologically diverse. These parasites exhibit high species diversity at the level of host species or individual fish specimens. Using case studies, especially those widely performed in Dactylogyrus parasitizing cyprinoid fish, this article presents current knowledge on the ecology and evolution of congeneric gill monogeneans. The important aspects of the ecology of congeneric monogeneans are highlighted, in particular: host specificity expressed at several host levels (from strict specificity to phylogenetic specificity), microhabitat specificity expressed by restricted positions on fish gills to facilitate intraspecific mating, and the link between microhabitat preference and morphological adaptation (i.e., sclerotized structures of the haptor) or reproductive isolation. From the evolutionary perspective, this study focused on the processes of the speciation and diversification of congeneric monogeneans, highlighting the role of host switch as the most prominent coevolutionary event, accompanied in some cases mostly by intrahost speciation or cospeciation, as revealed by cophylogenetic studies. Here, important knowledge on evolutionary patterns of host specificity, microhabitat specificity, and morphological adaptation is presented. Host-specific monogeneans may represent an important tool for studying the historical biogeography of their hosts. Specifically, in the case of freshwater fish hosts exhibiting disjunctive distribution, they reflect both historical and contemporary contacts. The role of host-specific congeneric monogeneans in revealing historical intercontinental and intracontinental contacts between freshwater fish is highlighted. Finally, the importance of the role of genetic coadaptation, limiting the presence of host-specific monogeneans in hybrid fish, is emphasized.
Keywords: druhová specificita; Fish parasites; Fish Diseases; Host specificity; Host-Parasite Interactions; Ecosystem; fylogeneze; interakce hostitele a parazita; Platyhelminths; Phylogeny; infekce červy třídy Trematoda; Genetic coadaptation; biologická evoluce; sladká voda; Fresh Water; Species Specificity; ryby; Fishes; hostitelská specificita; Animals; Host-parasite coevolution; Biological Evolution; Species coexistence; zvířata; nemoci ryb; Trematoda; ploštěnci; Monogeneans; ekosystém; Gills; Trematode Infections; žábry; Host Specificity